LabVIEW toolkit implementation of MIMO-OFDM - Chen, Yao. (2010)
Nowadays, Information Technology has become part of our life, wireless communication play an important role of it. A combination of multiple-input multiple-output (MIMO) system and orthogonal frequency division multiplexing (OFDM) system is a popular technology in wireless communication field in the world. It combines the advantages of both MIMO and OFDM technology. It provides very high data rates; and prevents narrow-band co-channel interference, intersybmol interference and fading caused by multipath propagation, provides high spectral efficiency, low sensitivity to time synchronization errors. In this project, there are two parts. Firstly, the fundamental theory of MIMO-OFDM system is studied. Secondly, the Matlab code, which has been developed to demonstrate the MIMO-OFDM system, is converted into LabVIEW programs by using a MIMO-OFDM broadband wireless testbed based on the National Instruments PXI platform.